Activation of gingival fibroblasts by bacterial cyclic dinucleotides and lipopolysaccharide - Elmanfi S; Sintim HO; Zhou J; Gürsoy M; Könönen E; Gürsoy UK (Switzerland, 2022)
Human gingival fibroblasts (HGFs) recognize microbe-associated molecular patterns (MAMPs) and respond with inflammatory proteins. Simultaneous impacts of bacterial cyclic di-guanosine monophosphate (c-di-GMP), cyclic di-adenosine monophosphate (c-di-AMP), and lipopolysaccharide (LPS) on gingival keratinocytes have been previously demonstrated, but the effects of these MAMPs on other periodontal cell types, such as gingival fibroblasts, remain to be clarified. The present aim was to examine the independent and combined effects of these cyclic dinucleotides and LPS on interleukin (IL) and matrix metalloproteinase (MMP) response of HGFs. The cells were incubated with c-di-GMP and c-di-AMP, either in the presence or absence of Porphyromonas gingivalis LPS, for 2 h and 24 h. The levels of IL-8, -10, and -34, and MMP-1, -2, and -3 secreted were measured by the Luminex technique. LPS alone or together with cyclic dinucleotides elevated IL-8 levels. IL-10 levels were significantly increased in the presence of c-di-GMP and LPS after 2 h but disappeared after 24 h of incubation. Concurrent treatment of c-di-AMP and LPS elevated MMP-1 levels, whereas c-di-GMP with LPS suppressed MMP-2 levels but increased MMP-3 levels. To conclude, we produce evidence that cyclic dinucleotides interact with LPS-mediated early response of gingival fibroblasts, while late cellular response is mainly regulated by LPS.